THE PROBLEMS OF FAIR AND EQUITABLE TREATMENT STANDARD IN THE ENERGY CHARTER TREATY - Kuzhatov, Багдат Гиззатович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2021)
The fair and equitable treatment standard (hereinafter referred to as the Standard) is one of the controversial standards for the protection of investors' rights in international investment law and the subject of intense scientific discussions. Recent changes in the international investment treaty regime, in response to growing concerns about host countries' right to regulation and investor-government dispute settlement system, have prompted a revision of longstanding provisions of the Standard. The Energy Charter Treaty (hereinafter referred to as the Treaty) is an example of such a revision. In November 2017, the Energy Charter Conference decided in Ashgabat to start discussions on the potential modernization of the ECT. On November 27, 2018, the Energy Charter Conference approved a list of topics for modernizing the ECT. The standard is one of them. This research article aims to review the current provisions of the Standard in light of the Energy Charter Treaty). In the article the author analyzes the current regime of the Standard and identifies its problems. The article also discusses the advantages and disadvantages of these approaches. In conclusion, the author substantiates the applicability of one or another approach in relation to the Treaty. The scientific novelty of the article is determined by the fact that this study is devoted to a critical analysis of the current regime of the Standard in the Treaty. The subject of the research is international investment law and international energy law, in particular the regime of treaties on investment protection. The article uses the doctrinal methodology of legal research from the standpoint of historical, comparative and empirical analysis. The research in this article is text-based and, where applicable, supported by empirical research. Keywords: investment protection, fair and equitable treatment, the Energy Charter Treaty, European Union, energy disputes.